Women Trafficking: Young Women’s Perspectives in West Java, Indonesia - Widiasih, Restuning; Ermiati, Ermiati; Emaliyawati, Etika; Sutini, Titin; Setyawati, Anita; Rahayu, Urip (Jurnal Keperawatan Soedirman, 2018)
ABSTRACTWest Java province is the most contributors of women trafficking cases in Indonesia. Women trafficking threaten women in all age group, including young women. However, little is known young women’s perspectives of women trafficking especially in West Java region. The aim of this study was to determine young women’s perspectives of the impact of trafficking, and their actions to prevent it. This was a descriptive quantitative study. This study involved 361 young women ages 15-17 who chosen using the stratified random sampling technique. Respondents filled up questionnaire. Data were analysed using distribution of frequency. The study revealed that 65% of young women perceived that trafficking had negative impact to their health, and 71 % of them were also of the view that individual prevention was necessary. However, only 30 % of them perceived the importance of social support actions to prevent women trafficking. This study conclude that young women had different perceptions about impact of trafficking and actions to prevent it. There is a need of effective strategies to improve social support for preventing women’s trafficking. Enhancing women’s awareness, perceptions, and knowledge of human trafficking especially in West Java is also necessary.